Dust Populations from 30 to 1000 Au in the Debris Disk of Hd 120326 Panchromatic View with Vlt/Sphere, Alma, and Hst/Stis - Miley, J (EDP Sciences, 2025)
Context. To date, more than a hundred debris disks have been spatially resolved. Among them, the young system HD 120326 stands out, displaying different disk substructures on both intermediate (30–150 au) and large (150–1000 au) scales. Aims. We present new VLT/SPHERE (1.0–1.8 µm) and ALMA (1.3 mm) data of the debris disk around HD 120326. By combining them with archival HST/STIS (0.2–1.0 µm) and archival SPHERE data, we have been able to examine the morphology and photometry of the debris disk, along with its dust properties. Methods. We present the open-access code MoDiSc (Modeling Disks in Scattered light) to model the inner belt jointly using the SPHERE polarized and total intensity observations. Separately, we modeled the ALMA data and the spectral energy distribution (SED). We combined the results of both these analyses with the STIS data to determine the global architecture of HD 120326. Results. For the inner belt, identified as a planetesimal belt, we derived a semi-major axis of 43 au, fractional luminosity of 1.8 × 10−3, and maximum degree of polarization of 51% ± 6% at 1.6 µm. The spectral slope of its reflectance spectrum is red between 1.0 and 1.3 µm and gray between 1.3 and 1.8 µm. Additionally, the SPHERE data show that there could be a halo of small particles or a second belt at distances ≤150 au. Using ALMA, we derived in the continuum (1.3 mm) an integrated flux of 561 ± 20 µJy. We did not detect any 12CO emission. At larger separations (>150 au), we highlight a spiral-like feature spanning hundreds of astronomical units in the STIS data. Conclusions. Further data are needed to confirm and better constrain the dust properties and global morphology of HD 120326. © The Authors 2025.